2021
DOI: 10.1002/cncr.33602
|View full text |Cite|
|
Sign up to set email alerts
|

Risks of subsequent primary cancers among breast cancer survivors according to hormone receptor status

Abstract: Background This study was aimed at examining the risks of subsequent primary cancers (SPCs) among breast cancer survivors by hormone receptor (HR) status and age at diagnosis. Methods Data from 12 Surveillance, Epidemiology, and End Results registries were used to identify 431,222 breast cancer survivors (at least 1 year) diagnosed between the ages of 20 and 84 years from 1992 to 2015. Risks of SPCs were measured as the standardized incidence ratio (SIR) and the excess absolute risk (EAR) per 10,000 person‐yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 70 publications
3
43
0
Order By: Relevance
“…This indicates that in the case of distant MBC patients, analysis of lung lesions as primary or metastasis is essential; hence, SPCs should be considered. A significantly higher risk of second primary thyroid cancer was also observed in our study, which is consistent with previous studies ( 21 23 ). Moreover, our results show a gradient in risk with metastatic modality (SIR: NMBC: 1.72 vs. MBC-regional node: 2.35 vs. MBC-distant organ: 2.77), and the prognosis of distant MBC was poor after diagnosis with second primary thyroid cancer.…”
Section: Discussionsupporting
confidence: 94%
“…This indicates that in the case of distant MBC patients, analysis of lung lesions as primary or metastasis is essential; hence, SPCs should be considered. A significantly higher risk of second primary thyroid cancer was also observed in our study, which is consistent with previous studies ( 21 23 ). Moreover, our results show a gradient in risk with metastatic modality (SIR: NMBC: 1.72 vs. MBC-regional node: 2.35 vs. MBC-distant organ: 2.77), and the prognosis of distant MBC was poor after diagnosis with second primary thyroid cancer.…”
Section: Discussionsupporting
confidence: 94%
“…All breast cancer patients, independent of radiotherapy, have a higher risk to develop second cancers, most commonly of the lung, esophagus and thyroid compared to the general population [ 41 , 42 ]. This risk increases considerably for irradiated patients [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of SNBPC has been evaluated in several studies from diverse populations [6][7][8][9][10][11][12][13][14][16][17][18][19]. The studies examined databases from various sources, including nationwide population-based data, regional registries, or institutional cohorts, to obtain comprehensive information on SNBPC (Table 6).…”
Section: Korean Cancer Associationmentioning
confidence: 99%
“…Previous studies have shown that various types of SNBPC occurred after breast cancer treatment [6][7][8][9][10][11][12][13]. Moreover, the risk of developing SNBPC among survivors of breast cancer significantly exceeds that in women without cancer in the general population [8,11,14]. Furthermore, patients with SNBPC may come across complicated medical issues caused by a previous treatment for breast cancer.…”
Section: Introductionmentioning
confidence: 99%